Phenomenon of Dark Space - Antonov, Alexander Alexandrovich (Newest Updates in Physical Science Research Vol. 1, 2021)
The phenomena of dark matter and dark energy are the most significant scientific discoveries of the 20th century in astrophysics. But until very recently they were completely inexplicable. And nevertheless, attempts to explain them still continue to be made mainly with the help of research at the Large Hadron Collider. At the present time in astrophysics it is generally accepted that the phenomena of dark matter and dark energy can be explained by the existence of some still unknown physical entities only in our visible universe. Moreover, this assumption seems to be quite reasonable, since the Monoverse hypothesis following from the postulate about non-exceedance of the speed of light in the special theory of relativity, leaves no place for dark matter and dark energy nowhere, except in our visible universe. However, in fact, this assumption is erroneous, because, as shown in the article, dark matter and dark energy are just gravitational images of invisible parallel universes coexisting with our visible universe in the Multiverse, which is therefore called hidden. The study, which made it possible to prove this, was carried out using previously unknown radio-electronic experiments that proved the general scientific principle of the physical reality of imaginary numbers. And this principle in the existing version of the special theory of relativity refuted the postulate of non-exceeding the speed of light, as well as the statement following from it about the existence of the Monoverse. It also made it possible to detect the fallacy of existing relativistic formulas and correct them. And from the corrected relativistic formulas the existence of the hidden Multiverse follows. Moreover, the mathematical analysis of the experimental data obtained by the WMAP and Planck spacecraft made it possible to prove that in nature, in addition to the invisible universes of the hidden Multiverse, there are other invisible universes connected with it through portals, creating the phenomenon of dark space. And the Multiverses of the dark space together with the hidden Multiverse form the Hyperverse. The article shows that the existence of invisible universes included in these Multiverses can be experimentally proved by astronomical observations in portals.